Strategies to Enhance the Productivity of an Automotive Company Throughout the Supplier Selection Process Method - Yurika, Nadilla; Muhamar, Heris; Ananda, Indhy Agustya (Journal of International Conference Proceedings, 2024)
The study aims to determine strategies for selecting suppliers to improve productivity at the Automotive Company. Supplier selection methods are vital for purchasing and procurement departments, as they directly influence organizational success. By carefully assessing suppliers, these departments can ensure cost efficiency by negotiating favorable terms and prices and guaranteeing high-quality products or services that meet established standards. By employing qualitative research methods, the research scrutinizes the criteria, decision-making processes, and challenges in selecting suppliers through analysis of the methods. The findings of this research contribute to the existing body of knowledge by offering valuable insights and practical implications for improving supplier selection processes within automotive companies. This research identifies and ranks criteria for supplier selection and monitoring, as well as explains where supplier selection strategies could be improved, with the ultimate goal of improving supply chain management and overall organizational performance in the automotive sector.